Color stability of Lucirin-photo-activated resin composite after immersion in different staining solutions: a spectrophotometric study - AlSheikh R (Dove Medical Press, 2019)
Rasha AlSheikh Restorative Dental Sciences Department, College of Dentistry, Imam Abdulrahman Bin Faisal University, Dammam, Saudi ArabiaCorrespondence: Rasha AlSheikhRestorative Dental Sciences Department, College of Dentistry, Imam Abdulrahman Bin Faisal University, Po Box 30018 AlKhobar, Dammam 31952, Saudi ArabiaEmail ralsheikh@iau.edu.saIntroduction: Exceptional optical properties characterize teeth. As such, an esthetic restorative material should enable the dental professional to imitate the optical properties of natural teeth accurately. IPS Empress Direct was introduced to the market with the claim that it can mimic optically dental tissues with superior clinical performance.Aim: To evaluate the ability of IPS Empress Direct to mimic tooth appearance and color and resist staining.Materials and methods: Three disc specimens were prepared for each shade of enamel and dentin of Lucirin-based composite, IPS Empress Direct (Ivoclar Vivadent) (A1, A2, A3, B1, and B2) (total of 60). The specimens were submitted to colorimetric evaluation in comparison after immersion in 10 different solutions (coffee, coffee with sugar, coffee with milk, red tea, red tea with sugar, red tea with milk, tomato juice, pomegranate juice, coke, and distilled water as a control group) for 4 weeks using spectrophotometric analysis.Results: After plotting the data and conducting linear regression analyses, IPS Empress showed high potential in mimicking the optical properties of natural tooth color according to the CIE color space. Three solutions showed a change in color higher than 3, coffee, coffee with sugar, and red tea. All other solution showed changes in color that are acceptable clinically.Conclusion: IPS Empress Direct can satisfactory mimic teeth appearance and color while manifesting high stability of color resisting staining upon clinical aging.Keywords: composite color, composite shade, restoration staining, IPS Empress